1992
DOI: 10.1111/j.1365-2591.1992.tb00750.x
|View full text |Cite
|
Sign up to set email alerts
|

Tissue responses assessed by intramuscular implantation

Abstract: Freshly mixed polymerized Hydron root canal filling material, fully set AH26 and Teflon were implanted in the quadriceps muscle of guinea pigs and assessed histologically at 2 days, 1, 2, 3, 12 and 26 weeks after implantation. All materials were characterized by peri-implant fibrous connective tissue capsule formation. Von Kossa-positive calcific material was observed at the implant-tissue interface of Hydron implants. The amount of apparently calcified material increased with time. Inflammation was not a prom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1992
1992
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…An interesting question remains: is this disturbance of cytokine levels only caused by the initial trauma of catheter insertion, or is it further augmented by the remaining foreign body of the catheter? The catheter used is made out of FEP-Teflon, a material extensively tested for its biocompatibility that has not been shown to provoke any significant inflammatory tissue reaction or foreign body granuloma formation in vivo (6,16,22). According to the literature, we hypothesize for the present investigation that the cytokine response is primarily initiated by the initial trauma caused by the catheter insertion.…”
Section: Discussionmentioning
confidence: 94%
“…An interesting question remains: is this disturbance of cytokine levels only caused by the initial trauma of catheter insertion, or is it further augmented by the remaining foreign body of the catheter? The catheter used is made out of FEP-Teflon, a material extensively tested for its biocompatibility that has not been shown to provoke any significant inflammatory tissue reaction or foreign body granuloma formation in vivo (6,16,22). According to the literature, we hypothesize for the present investigation that the cytokine response is primarily initiated by the initial trauma caused by the catheter insertion.…”
Section: Discussionmentioning
confidence: 94%
“…Their conclusion regarding lack of conformity to root canal regularities and shrinkage resulted in the histological study of three experimental root canal materials; root filling consisting of silicone elastomer and adhesive (Silastic 382 elastomer and Silastic Medical Adhesive type A) or a pure polyhydroxy-ethyl-methacrylate root filling (Hydron, Hydron Technologies, FL, USA ) (185). The in vitro & in vivo preliminary findings for Hydron were very promising [192][193][194], but a subsequent long-term study showed poorer results with Hydron versus gutta-percha and AH-26 [195]. Furthermore, other independent studies on histological responses and leakage found that Hydron did not fulfill the manufactures promises concerning physical/clinical properties as it elicited severe inflammatory responses, demonstrated more leakage than conventional root filling materials, and was resorbable [196][197][198].…”
Section: Faculty Of Dentistry | University Of Oslo | 2018mentioning
confidence: 99%